Based on Pearson correlation coefficient and Monte Carlo simulation method, the calculation formula of frictional resistance is optimized for soft shaft bending and pulling of steel wire. Issue 1 (May 2021) - Wang, Tengfei; Li, Jian; Liu, Yisheng
Abstract: The main content of this study is based on Pearson correlation coefficient and Monte Carlo simulation method to optimize the frictional resistance calculation formula for pushing and pulling flexible wire shafts in different bending states. According to the calculation formula and experimental data of the frictional resistance of the soft shaft bending of the wire, in order to improve the calculation accuracy, the Pearson correlation coefficient test is carried out by f f =μD βP y n /1 + y 2 SPSS software, and the coefficient β and the corresponding friction f between the shaft core and the sheath are very relevant at all angles, so the size of the β can be adjusted to make the calculation of friction f more accurate. The parameters and parameters of the formula β modified by the Monte Carlo simulation method, and the frictional resistance formula of the flexible wire rope shaft at different angles is optimized. The optimized formula is calculated with an overall error of 2.3260%, which is 1.5637% lower than the original total error of 3.8898%, and is suitable for soft shaft friction with different diameters at a certain calculation angle.